Critical approaches to ‘clerical’ work: Textual transmission in two Swedish digital resources - Martinez, Merisa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
In this paper, we investigate the distinction between library digitization projects and digital scholarly editing projects by using qualitative interview data gathered from two Swedish digital scholarship ecosystems: 1) Litterarturbanken (the Swedish Literature Bank) and its collaboration with Gothenburg University Library, and 2) the internal collaboration at Uppsala University Library and the resulting digital output on the ALVIN platform. After examining the elements of digital editing practice that show up in each of these collaborations, we argue that these distinctions are blurring, and we call for a reorientation from critical versus noncritical editing towards critical transmission activities, which allows more room for less easily definable digital publishing projects to be examined. Further, we conclude that librarians, library-based textual scholars, and library technologists such as image technicians, digitization coordinators, and photographers are actively participating in the critical transmission of literary texts and the reframing of the institutionally enforced boundaries between the terms ‘librarian’ and ‘scholar.’